Land Use Change Analisys And Land Use Prediction On Markov Chain Method In Bungo Regency - Lili Suryani (Baselang, 2023)
Land use change commonly occurs as a logical consequence of regional development. Widely known drivers include government policies, as well as physical, social and economic causes. The research sets its goals to (1) Identify land use change in Bungo Regency between 1993, and 2011; (2) Predict 2011 and 2025 land use based on Markov Chain and measure their accuracies; (3) Evaluate the regency’s 2001-2011 land allocation.This research found that land use in Bungo was substantially altered during 1993-2011 period. Forest declined about 87,754 Ha or about 18.84% of the test site. Three biggest raises were oil palm plantation (8.84%), rubber plantation (5.89%) and upland agriculture (2.23%).Based on the results of the multinomial logit analysis, it is indicated that the factors that play a real role at the 70% confidence level, the additional factor is the distance of the regent street. These included distance to regency-managed road, slope, soil type, and land allocation in spatial planning. In general, this research suggested that about 44.1% of 2011 land use was in agreement to respective land allocation. It was discovered that Markov Chain was able to predict 2011 land use in high precision (about 98.5%).